Peningkatan Layanan Aplikasi Spotify Menggunakan Naïve Bayes - Wahyuni, Era; Suhartana, I Ketut Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p20, 2022)
Spotify is a platform that provides services for listening to music digitally that can be downloaded through the Google Play Store and The App Store can also be downloaded for PC. Currently, Spotify has 433 million users. With so many users, it is certainly inseparable from the reviews or ratings given to the Spotify application which will also have an impact on the platform. In order to improve the service to be better, these reviews need to be reviewed so that users are more comfortable in using the application. Through this research, it will be known the performance of the Naïve Bayes algorithm in conducting sentiment analysis on user reviews of the Spotify application on the Google Play Store. The results of this study show that the accuracy value of using Naïve Bayes is 85% from a ratio of 70:30 training data and testing data using a music dataset from 1 January 2022 to 9 July 2022, there were 61586 reviews from users taken from the Kaggle website.